2015
DOI: 10.5114/ceji.2015.52839
|View full text |Cite
|
Sign up to set email alerts
|

Review paper Angiomodulatory properties of Rhodiola spp. and other natural antioxidants

Abstract: Disturbances of angiogenesis and oxidative stress can lead to many serious diseases such as cancer, diabetes or ischemic heart disease. Substances neutralizing oxidative stress are known as antioxidants. They can affect angiogenesis process also, and thus, they modulate therapy results. Antioxidants become more and more frequently used in order to maintain homeostasis of the organism and diminish the risk of disease. Herein, we introduce some antioxidant preparations of natural plant origin (Rhodiola, Aloe ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 104 publications
0
27
0
Order By: Relevance
“…Resveratrol-induced autophagy in ARPE-19 cells as shown by increased autolysosome formation and autophagy flux, as well as change in the LC3 and p62 protein levels [13] in our study could be further confirmed by TEM. ARPE-19 cells have also been used to show the anti-inflammatory potential of resveratrol through the decrease of IL-6 and IL-8 expression, as well as to show its anti-oxidative properties by exhibiting a cytoprotective effects against the enhancement of IL-8, MCP-1, and VEGF secretion and anti-angiogenic potential by the inhibition of VEGF-A secretion [21,25]. Our results are in agreement with these findings and expand upon the repertoire of other inflammation-and angiogenesis-related factors attenuated by resveratrol (e.g., DKK-1; HGF; IGFBP-2 and 3; IL-11 and 17A; Pentraxin-3).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol-induced autophagy in ARPE-19 cells as shown by increased autolysosome formation and autophagy flux, as well as change in the LC3 and p62 protein levels [13] in our study could be further confirmed by TEM. ARPE-19 cells have also been used to show the anti-inflammatory potential of resveratrol through the decrease of IL-6 and IL-8 expression, as well as to show its anti-oxidative properties by exhibiting a cytoprotective effects against the enhancement of IL-8, MCP-1, and VEGF secretion and anti-angiogenic potential by the inhibition of VEGF-A secretion [21,25]. Our results are in agreement with these findings and expand upon the repertoire of other inflammation-and angiogenesis-related factors attenuated by resveratrol (e.g., DKK-1; HGF; IGFBP-2 and 3; IL-11 and 17A; Pentraxin-3).…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro studies using co-culturing of mouse endothelial and L-1 sarcoma cells, Rhodiola extracts inhibited proliferation and migration of endothelial cells [84]. Rhodiola extracts and salidroside and rosavin were also shown to inhibit in vivo neovascularization that was induced by the implantation of syngeneic tumor cells [84] or human kidney cancer homogenate [114]. …”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…& C. A.Mey. is used in traditional Mongolian medicine, but has been poorly investigated from a phytochemical and pharmacological perspective [6]. In 2010, Panossian et al [7] published a systematic review of clinical trials to evaluate the level of scientific evidence for the efficacy of R. rosea in the treatment of specific conditions (fatigue, depression).…”
Section: Abstract !mentioning
confidence: 99%
“…In addition, the modulatory effects of Rhodiola spp. and other natural antioxidants on angiogenesis have also been recently reviewed [6]. Apart from their adaptogenic properties, it seems that Rhodiola species also have antitumoral and antiproliferative effects, protecting tissues against free radicals and weak and medium-strength mutagens.…”
Section: Abstract !mentioning
confidence: 99%